1995
DOI: 10.1002/etc.5620140524
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of standard acute toxicity tests with rapid‐screening toxicity tests

Abstract: This study compared the relative sensitivity of five inexpensive, rapid toxicity tests to the sensitivity of five standard aquatic acute toxicity tests through literature review and testing. The rapid toxicity tests utilized organisms that require little culturing or handling prior to testing: a freshwater rotifer (Branchionus calyciflorus); brine shrimp (Artemia salina); lettuce (Lactuca sativa); and two microbial tests (Photobacterium phosphoreum–Microtoxr̀ test, and a mixture of bacterial species–the Polyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(45 citation statements)
references
References 73 publications
1
44
0
Order By: Relevance
“…The Microtox ® test is considered relatively inexpensive, provides well-reproducible results, and offers a fast testing procedure. The toxicity data obtained with the Microtox ® test correspond well with acute toxicities obtained with standard toxicity tests for many bioassayed samples (Kaiser and Palabrica, 1991;Toussaint et al, 1995;Weideborg et al, 1997). This Microtox ® biotest has been widely used recently to investigate the toxicity of various inorganic and organic compounds in water samples (Trang et al, 2005;Gueune et al, 2009;Katritzky et al, 2010).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The Microtox ® test is considered relatively inexpensive, provides well-reproducible results, and offers a fast testing procedure. The toxicity data obtained with the Microtox ® test correspond well with acute toxicities obtained with standard toxicity tests for many bioassayed samples (Kaiser and Palabrica, 1991;Toussaint et al, 1995;Weideborg et al, 1997). This Microtox ® biotest has been widely used recently to investigate the toxicity of various inorganic and organic compounds in water samples (Trang et al, 2005;Gueune et al, 2009;Katritzky et al, 2010).…”
Section: Introductionsupporting
confidence: 65%
“…Many comparative studies with more widely used biological testing procedures, such as acute daphnid/fish tests, have been conducted to evaluate the applicability of the Microtox ® assay in environmental pollution monitoring (Dutka and Kwan, 1981;Lebsack et al, 1981;Curtis et al, 1982;Qureshi et al, 1982;Miller et al, 1985;Toussaint et al, 1995;Wӓngberg et al, 1995;Sweet et al, 1997;Doherty et al, 1999). Bulich et al (1981) Although the toxicity of individual heavy metals has been assessed in many studies, little effort has been made to understand the environmental impact of these heavy metals in combination, as is usually the case in the natural environment (Soetaert et al, 2007), where the interaction between different compounds can highly influence the overall toxic impact of the heavy metal stressors on the organisms present.…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%
“…Raw leachate was found to be toxic only for L.sativa. Studies have found that the lettuce seed is very sensitive to the presence of metals and organic compounds, which makes it suitable for testing the toxicity of effluents (Wang, 1987;Toussaint et al, 1995). The inhibition of L. sativa root growth in raw leachate samples has also been reported by Žaltauskaitė and Čypaitė (2008), with root growth inhibition reaching up to 80%, when compared to the control.…”
Section: Discussionmentioning
confidence: 78%
“…These were chosen as they are commonly used species with a strong body of supporting literature from previous stud-Ž . ies Pillard et al, 1996;Toussaint et al, 1992 .…”
Section: Chemical Analysis and Experimentsmentioning
confidence: 99%